2021
DOI: 10.1111/cid.13035
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, radiographic, and immunological evaluation of angulated screw‐retained and cemented single‐implant crowns in the esthetic region: A 1‐year randomized controlled clinical trial

Abstract: Background: Screw-retained implant crowns are considered more biologically compatible than cemented crowns due to the absence of excess cement. However, traditional screw-retained implant crowns are not viable when the access hole of the screw channel would need to be located in an esthetic area, which would compromise the esthetic outcome of the treatment.Purpose: To evaluate the clinical, radiographic, and immunological outcomes of angulated screw-retained and cemented single-implant crowns in the esthetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
3
11
0
Order By: Relevance
“…Implants were placed to support a screw-retained prosthesis. The effect of prosthetic solutions that may compensate up several degrees of axial discrepancy 27,28 and, subsequently, reduce the need for bone augmentation was not assessed. After virtual implant placement was completed, additional bone augmentation was deemed necessary when a minimum of 1 mm of circumferential bone support was not observed around the whole implant fixture.…”
Section: Discussionmentioning
confidence: 99%
“…Implants were placed to support a screw-retained prosthesis. The effect of prosthetic solutions that may compensate up several degrees of axial discrepancy 27,28 and, subsequently, reduce the need for bone augmentation was not assessed. After virtual implant placement was completed, additional bone augmentation was deemed necessary when a minimum of 1 mm of circumferential bone support was not observed around the whole implant fixture.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few in vivo reports have reported on these restorations, and their results hint that this system can provide satisfying success and survival rates, even if at short follow-ups [21,29].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have found that ASC crowns would fail under the bite force exceeding physical chewing force, 8,17,20 it in line with previous clinical trials. 21,[30][31][32] No significantly different PES was found between RC group and ASC group (RC: 9.88 ± 2.11 vs ASC: 10.63 ± 3.49, p = 0.555). It indicates that ASC abutment (Nobel Biocare) has the same aesthetic effect with the RC abutment.…”
Section: Radiographic Assessmentmentioning
confidence: 99%
“…19 It was confirmed that ASC abutment have similar clinical acceptable effects as regular cemented abutment during short-term follow-up, 20 although the concentration of TNF-α in peri-implant crevicular fluid in the ASC group was significantly higher than regular cemented group while the bleeding of probe rate (BOP%) was lower in the ASC group. 21 Professor Friberg has revealed that there were only 0.41 mm marginal bone loss (MBL) in 1-year follow-up. 22 And a recent study showed that ASC crowns have comparable aesthetic and functional results after 44.3 months follow-up.…”
Section: Introductionmentioning
confidence: 99%